Inferring Transcription Factors and microRNAs Associated with Elevated Expression of the Oncogenic B-Cell Lymphoma 11A in Triple Negative Breast Cancer - Nouf N. Laqtom,; Khloud M. Algothmi,; Amani H. Bakhribah, (Journal of King Abdulaziz University: Medical Sciences, 2023)
B-cell lymphoma 11A, a transcriptional repressor, is highly expressed in triple negative breast cancer. The in vitro studies and animal models provide initial evidence suggesting that the knockdown of B-cell lymphoma 11A has a therapeutic eff ect on breast cancer. Defining the regulators driving the high expression of B-cell lymphoma 11A is important to understand its cancer-related functions. Among these regulators, transcription factors and microRNAs are critical for gene expression and associated with expression perturbations. Firstly, we identifi ed the transcription factors that potentially interact with B-cell lymphoma 11A promoter. Based on bioinformatics prediction and multiple Omics datasets, two upregulated transcriptional activators Zinc Finger BED-Type Containing 4 and E2F Transcription Factor 1 in triple negative breast cancer were found to have seven sites within B-cell lymphoma 11A promoter. Secondly, we aimed to determine a putative set of microRNA that can mediate the post-transcriptional repression of B-cell lymphoma 11A. miR-513a-5p, miR-139-5p, miR- 1179, miR-140-5p, and miR-542-3p, harboring at least one site of interaction with B-cell lymphoma 11A 3 untranslated region, were found inhibited in triple negative breast cancer. Taken together, the combinatorial regulation by transcription factors and microRNAs provide valuable information for further investigation on controlling the expression level of B-cell lymphoma 11A in triple negative breast cancer.